Sistem Informasi Akuntansi Siklus Pendapatan Pada Usaha Bengkel Budi Barokah Sokaraja - Imam Soleh Marifati; Ubaidillah Ubaidillah (Universitas Bina Sarana Informatika, 2019)
Abstract: Computer-based accounting information systems can be used by companies to improve the efficiency, effectiveness and accuracy of the processes of business transactions that occur in the company. The income accounting cycle which is one of the cycles in an accounting information system needs attention because this cycle produces revenue transactions which are a financial source for the company. The use of computer-based systems in this cycle can also provide added value in the form of improving services to customers. To implement a computer-based accounting information system, a software is needed to process revenue transactions. In this study, the authors developed an application of accounting information systems to process transactions in the income cycle found in vehicle workshop businesses. This application processes transaction data starting from ordering repair services, recording spare parts usage, repair service fees, bill payments and and making income reports on workshop business activities. Keywords: revenue cycle, repairation service, accounting information system